Genome-Wide Analysis of the Fatty Acid Desaturase Gene Family Reveals the Key Role of PfFAD3 in α-Linolenic Acid Biosynthesis in Perilla Seeds - Duan, Wu; Shi-Mei, Yang; Zhi-Wei, Shang; Jing, Xu; De-Gang, Zhao; Hong-Bin, Wang; Qi, Shen (Frontiers in Genetics, 2021)
Perilla (Perilla frutescens), a traditional medicinal and oilseed crop in Asia, contains extremely high levels of polyunsaturated α-linolenic acid (ALA) (up to 60.9%) in its seeds. ALA biosynthesis is a multistep process catalyzed by fatty acid desaturases (FADs), but the FAD gene family in perilla has not been systematically characterized. Here, we identified 42 PfFADs in the perilla genome and classified them into five subfamilies. Subfamily members of PfFADs had similar exon/intron structures, conserved domain sequences, subcellular localizations and cis-regulatory elements in their promoter regions. PfFADs also possessed various expression patterns. PfFAD3.1 was highly expressed in the middle stage of seed development, whereas PfFAD7/8.3 and PfFAD7/8.5 were highly expressed in leaf and later stages of seed development respectively. Phylogenetic analysis revealed that the evolutionary features coincided with the functionalization of different subfamilies of PUFA desaturase. Heterologous overexpression of PfFAD3.1 in Arabidopsis thaliana seeds increased ALA content by 17.68%-37.03%. These findings provided insights into the characteristics and functions of PfFAD genes in perilla.